PERANCANGAN KURSUS PEMBELAJARAN ONLINE BERBASIS WEB - Faisal Reza Febriansyah (2023)
The Online Course Learning Application "Space Learning" is an innovative web-based platform designed to support online teaching and learning processes. The goal of this app is to provide an interactive, flexible, and effective learning experience for students, students, and mentors. In developing this application, we designed and implemented features that cover several important aspects of online learning. These features include users (admins, students, and mentors), module materials (upload and download), forum discussions, transactions, and assessments. Through the Ruang Belajar application, students can easily find a variety of courses and learning materials. They can download materials, interact with mentors through consultation features and chat media, and share knowledge with other students through discussion forums. In addition, the existence of a transaction system makes it easier for students to take additional class courses to improve their individual skills. For mentors, the Ruang Belajar application provides a tool that makes it easier for them to convey material, assign assignments, and provide feedback to students. This helps mentors manage classes efficiently and ensure optimal teaching quality. The Ruang Belajar application also provides benefits in utilizing students' additional time outside of class hours by providing exercises, questions, and additional material that can be accessed at any time. This helps students become more independent in acquiring knowledge and improving their skills. Through testing with the black box testing method, the Ruanglearning application has been tested to ensure that the existing features operate as expected. The test results show that this application is able to provide an effective learning experience and meet user needs. Thus, the Ruang Belajar online learning course application is expected to be a relevant solution in improving the teaching and learning process in this digital era.